All about that tweet: student perceptions of professors' social media use in the classroom. Issue 2 (13th June 2016) - Merle, Patrick; Freberg, Karen
Abstract : Purpose: The purpose of this study is to explore whether public relations professors' presence on social media and the inclusion of a social media assignment influence students' perceptions of a course. Design/methodology/approach: The experimental portion of this investigation consisted of a 2 (the presence or absence of a professor's social media accounts) × 2 (the presence or absence of a social media assignment) factorial design resulting in four conditions. Findings: The presence of a social media assignment positively influences students' intent to register for a public relations course. Research limitations/implications: The manipulation of a professor's social media use and the inclusion of a social media assignment might have been too subtle. A more explicit scenario might elicit more reactions from the participants. Practical implications: This study discussed key findings and best practices for professors who may want to use social media and the use of social media assignments in the classroom. Originality/value: This experimental investigation emerged from a distinct need to understand whether university students expect their professors to engage in social media activities.